Penguatan Kesiapsiagaan Bencana Melalui Pendidikan Mitigasi di SD Sungai Pedada, Tulung Selapan - Arni, Yusni; Wahyuningsih, Sri; Lia, Linda; Adelia Fitri, Elsi (PELITA NUSA TENGGARA, 2025)
Sungai Pedada Village, Tulung Selapan District, Ogan Komering Ilir Regency, is a water area that has a high potential for natural disasters such as floods, erosion, abrasion and other natural disasters. Challenging geographical conditions, limited access to electricity and transportation, and low awareness of the public, especially school children, on the importance of disaster mitigation are challenges in their efforts to improve the quality of education in Sungai Pedada schools. This community service activity aims to strengthen disaster preparedness through mitigation education for teachers and students. The implementation method includes the preparation stage, problem socialization, and training in the preparation of teaching materials. mentoring, evaluation, and reflection on activities. The results of the activity show that there is an increase in the knowledge and skills of teachers and students in understanding and applying the concept of natural disaster mitigation in the school environment. The use of teaching materials has been proven to increase students' interest in learning and involvement in the learning process, while strengthening their understanding of disaster preparedness measures. This activity is expected to be a model for the implementation of technology-based disaster mitigation education in remote areas, as well as support the realization of disaster resilient schools in the waters of the Pedada River.